Analisis Percepatan Waktu dan Produktivitas pada Proyek Pembangunan Kapal Baru di PT XYZ - Ardian Syahputra (Fakultas Teknik, 2025)
New shipbuilding is considered an important production process by the maritime industry that aims to produce ships that can meet market demand. In reality, problems often arise in the field that hinder the shipbuilding process, causing delays in completion. To overcome these problems, effective and efficient planning and scheduling are needed because they are the initial steps in project management. One method that can be applied is CCPM (Critical Chain Project Management) which can optimize project planning and avoid delays. This method can also ensure the project is completed according to the contract deadline. This method is used in one of the X1 tugboat construction projects at PT XYZ. This method uses a buffer time placed at the end of the project path and cuts safety time. The purpose of this study is to create a new schedule using the CCPM method that focuses on accelerating project duration, work productivity, and direct labor costs. The application of the CCPM method to the X1 tugboat project after cutting the safety time by 50% from the initial duration showed that the project duration scheduling accelerated by 39.35% compared to the initial project duration and work productivity increased from 1/mandays to 2/mandays and by the application of the CCPM method on direct labor costs becoming cost increase of 0.14%
Entry oleh Arif 2026 Maret 27
Keywords: Critical Chain Project Management; Scheduling; Productivity; New Ship Construction